Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang UMKM Di Pusat Niaga Palopo Di Kota Palopo - Ismail, Rahmy Nurhalizah; Hadrah, Hadrah; Rajiman, Widyawanti (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
This research aims to determine the factors that influence the income of MSME traders at the Palopo Commercial Center in Palopo City. In this research, location, and trading hours are independent variables, while income is the dependent variable. This research uses quantitative research methods by collecting data through observation and distributing questionnaires to 100 respondents consisting of MSME traders at the Palopo Commercial Center. The analysis method uses multiple linear regression analyses. The data obtained was then processed and tested using the SPSS application program. The research results show that: 1) The location variable has no effect and is not significant on the income of MSME traders. 2) The trading hours variable has a significant influence on the income of MSME traders. 3) The variables of location and trading hours have a simultaneous effect. The coefficient of determination test (R2) shows a value of 0.246, meaning that the income variable can be explained by the independent variable at 24.6% and dependence is influenced by other factors not examined in this research.